Effect of chromium supplementation, both organic and inorganic, on the growth capacity and genotoxicity of Labeo rohita - Sibgha Mubeen; Samreen Bibi; Maryum Zahra; Shah Jahan; Shahid Iqbal; Izma Iftikhar (International Journal of Multidisciplinary Sciences and Arts, 2022)
A control group, three groups treated with chromium chloride hexahydrate, and three groups supplemented with Cr-Pic were generated from labeorohita fingerlings. Results from the experimental group T4 that had been given 0.3 mg/kg of (Cr-Pic) and carbohydrates showed significance (P 0.05). In comparison to the control and other experimental groups, Labeo rohita showed superior growth. The aquaculture business has a minimal growth tendency, and the goal of fish feed formulation is to give fish a workable diet to improve their bodies. The biological machinery of fish relies heavily on organic and inorganic chromium compounds added to carbohydrates as an energy source. This article describes the impact of chromium picolinate (organic) and chromium chloride hexahydrate (inorganic) on Labeorohita's ability to grow and its genotoxicity. Seven groups (each with a replica) were used, with 30 each being watched in groups T5, T6, and T7. The results of the comet assay showed that fish erythrocytes had genetic damage according to dosage and Cr (organic or inorganic). So, by 0.31 mg/kg concentration, the greatest comet metrics (Tail length, Tail DNA, and Olive Tail Moment) were detected. This study suggested that organic Cr may be employed as a growth stimulator if inorganic Cr was hazardous. Overall findings suggested that organic chromium supplementation of 0.31 mg/kg should be reevaluated for growth. The goal of this research initiative is to encourage fish producers to use organic Cr-added feed because it increases yield while improving growth performance and has positive health impacts for customers that lower the danger of toxicity.